The Expectation Gap? A Case Study of New Employee in the Hong Kong Retail Banking Industry - Tong, Shuk Chong (2007)
This paper studies the discrepancy between pre-entry job expectation and post-entry actual perception of new employees in the Hong Kong retail banking industry. It investigates what new employees' expectations and perceptions are and how and why they diverge. Also, the relationship of the discrepancy between expectation and perception and work outcomes (job satisfaction and intention to quit) is found out. From the present study, it is found that new employees do not always hold inflated job expectations which suggested by past studies. They hold both higher and lower expectations compared to the reality in different job aspects. The significant areas of discrepancy which affect work outcomes are pay, task importance, work pressure, encouragement of free speech and fairness to employees. Lastly, suggestions to align discrepancies in these areas are also provided in this paper.